Potential Violations of the Right to a Good and Healthy Environment: The Impact of Granting Special Mining Permits on Religious Community Organizations - Kurdi, Kurdi; Joko Cahyono; Cut Zulfahnur Syafitri (Magister Hukum Universitas Semarang, 2025)
This study aims to critically examine the potential violations of the constitutional right to a good and healthy environment arising from the government’s policy of granting Special Mining Business Permit Areas (WIUPK) to religious community organizations. The urgency of this research is based on concerns that these organizations, lacking adequate technical competence, may exacerbate environmental degradation, perpetuate violations left by previous permit holders, hinder the transition to renewable energy, and obstruct access to justice for victims of environmental harm. Using a normative juridical method with legislative and conceptual approaches, this study analyzes the policy from the perspective of environmental human rights, a focus absent in prior research. The findings reveal that the policy has a strong potential to violate the right to a good and healthy environment and contradicts the state’s obligation to protect human rights as guaranteed by the 1945 Constitution. The novelty of this research lies in its emphasis on the conflict of interest between the traditional role of religious organizations as community advocates and their new role as mining operators. Therefore, it is recommended that the government review and revoke the priority granting scheme for WIUPK and consider alternative participation models for religious organizations through non-operational mechanisms such as community development funds or minority non-controlling share ownership.